The efficacy of EGFR gene mutation testing in various samples from non-small cell lung cancer patients: a multicenter retrospective study - Krawczyk, Paweł (J Cancer Res Clin Oncol, 2014)
INTRODUCTION: Testing for the epidermal growth factor receptor (EGFR) gene mutations requires considerable multidisciplinary experience of clinicians (for appropriate patient selection), pathologists (for selection of appropriate cytological or histological material) and geneticists (for performing and reporting reliable molecular tests). We present our experience on the efficacy of routine EGFR testing in various types of tumor samples and the frequency of EGFR mutations in a large series of Polish non-small cell lung cancer (NSCLC) patients. METHODS: Deletions in exon 19 and substitution L858R in exon 21 of EGFR gene were assessed using real-time PCR techniques in 1,138 small biopsies or cytological specimens and in 1,312 surgical samples. RESULTS: Out of 2,450 diagnostic samples (containing >10 % of tumor cells), the occurrence of EGFR gene mutations was 9 %; more frequently in women (13.9 %) and adenocarcinoma patients (10 %), particularly with accompanying expression of TTF1 (13.0 %). The frequency of EGFR gene mutations was similar in cytological and histological specimens, and in primary and metastatic lesions, and did not depend on the percentage of tumor cells and quality of isolated DNA. Cytological or small biopsy, compared to surgical specimens showed lower percentage of tumor cells, with no impact on the quality of real-time PCR assay. CONCLUSION: Cytological and small biopsy samples with low (10–20 %) content of tumor cells and specimens from metastatic lesions are a sufficient source for EGFR mutation testing in NSCLC patients. The incidence of EGFR gene mutations in examined population was similar to those reported in other Caucasian populations.